Social Relationships and Violence in Higher Education: Narrative Studies of Bullying Victims - Winda Nurlaila; Naila Salsabila (Yayasan Cerdas Pedia Indonesia, 2025)
This research addresses the escalating bullying epidemic within Indonesian higher education during the 2024-2025 period. While universities are theoretically intellectual sanctuaries, systemic violence has increasingly eroded student dignity. Utilizing a qualitative narrative inquiry approach, the study analyzes lived experiences from survivors, including high-profile cases at Diponegoro and Udayana universities. Theoretical frameworks include Social Control Theory and Ecological Systems Theory to examine how academic hierarchies normalize abuse. Findings indicate that violence is not merely interpersonal but a structural phenomenon rooted in a